Reluctance of Students to Utilize Virtual Educational Environments in Public Schools: Real World Experiences - Arouri, Yousef M.; Hamaidi, Diala A.; Aldrou’, Islam T.; Noufal, Rana K. (International Journal of Interactive Mobile Technologies (iJIM), 2024)
This study aimed to explore the perspectives of public-school students who were hesitant to use the Darsak Educational Platform (DEP) during the COVID-19 pandemic in order to understand their real-life experiences. To achieve the aim of the study, the researchers employed a qualitative approach in its phenomenological form. The study sample consisted of 12 male and female students from various public schools in Jordan. The participants were chosen using an intentional method. Semi-structured interviews were used to collect the data. The study’s findings revealed a variety of causes that contributed to students’ resistance to using DEP. These causes include the students’ lack of readiness to learn through DEP, the DEP’s failure to comply with international design standards, the inadequate physical and technical teaching environment, and the limited digital competencies of teachers needed in the virtual learning environment. Given the findings of this research, the researchers advise that additional consideration should be given to the design of DEP. They also advise providing students with appropriate guidance in the usage of educational platforms.